Workplace road safety risk management: An investigation into Australian practices - Warmerdam, A.; Newnam, S.; Sheppard, D.; Griffin, Mark; Stevenson, M. (Elsevier Ltd, 2017)
© 2016 Elsevier Ltd In Australia, more than 30% of the traffic volume can be attributed to work-related vehicles. Although work-related driver safety has been given increasing attention in the scientific literature, it is uncertain how well this knowledge has been translated into practice in industry. It is also unclear how current practice in industry can inform scientific knowledge. The aim of the research was to use a benchmarking tool developed by the National Road Safety Partnership Program to assess industry maturity in relation to risk management practices. A total of 83 managers from a range of small, medium and large organisations were recruited through the Victorian Work Authority. Semi-structured interviews aimed at eliciting information on current organisational practices, as well as policy and procedures around work-related driving were conducted and the data mapped onto the benchmarking tool. Overall, the results demonstrated varying levels of maturity of risk management practices across organisations, highlighting the need to build accountability within organisations, improve communication practices, improve journey management, reduce vehicle-related risk, improve driver competency through an effective workplace road safety management program and review organisational incident and infringement management. The findings of the study have important implications for industry and highlight the need to review current risk management practices.